Accuracy of electronic apex locator in the presence of different irrigating solutions - Padmanabh Jha; Vineeta Nikhil; Shalya Raj; Rohit Ravinder; Preeti Mishra (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to evaluate the accuracy of the apex locator in the presence of different irrigating solutions. Materials and Methods: Thirty humans, single canal mandibular premolars were decoronated, and canal orifices were flared with Gates-Glidden drills. Working length (Gold standard [GS]) was measured under ×3.5 magnification by inserting a size 10 K file until the tip became visible and deducting 0.5 mm from this length. Teeth were embedded in an alginate mass. Electronic apex locator (EAL) measurements were made with Propex II, while different irrigants were placed in the root canals with 30G needle and groups were made based on the type of irrigating solution used i.e., Group I (3% NaOCl), Group II (5% NaOCl), Group III (2% Chlorhexidine), and Group IV (17% ethylenediaminetetraacetic acid). Statistical analysis was performed. Results: Statistically insignificant differences were observed between the GS and EAL lengths among all the groups. There were significant differences (P < 0.05) only between Group III as compared to Group II and Group I. Conclusion: EAL can be used to accurately measure the working length, even in the presence of irrigating solutions. Of the irrigating solutions tested, least effect on the accuracy of EAL was seen with 2% chlorhexidine and the highest effect was seen with 5% NaOCl.